Secure and Reliable Data Transmission Over MANET Based On Principles of Computationally Secure Secret Sharing - Nikolay Ivanovitch Chervyakov; Maxim Anatolyevitch Deryabin; Anton Sergeevitch Nazarov; Mikhail Grigorievitch Babenko; Nikolay Nikolaevitch Kucherov; Andrei Vladimirovich Gladkov; Gleb Igorievitch Radchenko (Труды Института системного программирования РАН, 2019)
Mobile Ad-Hoc Networks (MANET) require special approaches to the design and selection of data transmission and security algorithms Nodes mobility and dynamic topology give rise to two key problems of MANET – the difficulty of ensuring confidentiality when transmitting data through a network and the complexity of organizing reliable data transfer. This paper proposes a new approach to organizing data transfer through MANET, based on node disjoint multipath routing and modular coding of data. Distributed modular coding allows the use of secret-sharing schemes to ensure confidentiality on the one hand and reliable coding on the other hand. In this paper, a Computationally Secure Secret Sharing Scheme based on the Residue Number System is used, which ensures the confidentiality of data and the reliability of their transmission. Such an approach also allows for balancing the network loading.